Delivering Aid Differently : Lessons from the Field - Kharas, Homi J., 1954-; Fengler, Wolfgang (Book collections on Project MUSE., 2010)
"Assesses the successes and failures of foreign aid programs, with an overview and examination of joint aid strategies, information systems, and lessons learned by experts from Brookings Institution and World Bank, with case studies from scholars and practitioners who reside in the recipient countries (Indonesia, Cambodia, Ethiopia, Kenya, Pakistan, Tajikistan)"--Provided by publisher